Management of Expired Liquid Chemicals in Gunung Batu's Chemistry Laboratory of Health Polytechnic of the Ministry of Health Bandung in 2018 - Anantamia Arbiana; Rochana Tsaralatifah; Novita Nuraeni (Universitas Airlangga, 2020)
Introduction: Hazardous waste materials can be generated from laboratory use sourced from expired chemicals. The purpose of this study examines how the management of expired chemicals in Gunung Batu's chemistry laboratory of Health Polytechnic of the Ministry of Health Bandung. Method: This study used descriptive case study observational design. The study population was all chemistry laboratory managers and all expired liquid chemicals of Health Polytechnic of the Ministry of Health Bandung in 2018 with a total sampling method. The variables studied were volume, the amount based on its characteristics, reduction stage, packaging stage, storage stage, collection stage, utilization stage, processing stage, and accumulation of liquid chemicals. The laboratories studied were the environmental health, nutrition, and health analyst laboratory. The result of interviews and observations collected data collection, and then it was used to analyze. Result and Discussion: The results of the expired liquid chemical volume measurement at Gunung Batu's chemistry laboratory Health Polytechnic of the Ministry of Health Bandung in 2018, were 108,138 milliliters. The expired liquid chemical measurement results based on their characteristics obtained results as many as 4.2% explosive, 50% flammable, 33.3% corrosive, and 12.5% toxic. According to observations and interviews, the chemistry laboratory has not implemented seven stages of chemical management correctly. Conclusion: The management of expired liquid chemicals in Gunung Batu's chemistry laboratory at Health Polytechnic of the Ministry of Health Bandung in 2018, does not fulfill the requirements.